Ompok supernus, a new catfish (Teleostei: Siluridae) from Borneo - Ng, Heok Hee (Zootaxa, 2008)
Ompok supernus, a new species of silurid catfish is described from the Rungan River drainage in Kalimantan Tengah, southern Borneo. Ompok supernus can be distinguished from all Southeast Asian congeners, except for O. borneensis, O. fumidus and O. leiacanthus, in having a combination of a brown body without any prominent black humeral spot, the rictal lobes separated by a superficial groove extending from the corner of the mouth to the submandibular groove, a gape not reaching beyond the anterior border of the orbit, and 54–66 anal-fin rays. Ompok supernus differs from O. borneensis, O. fumidus and O. leiacanthus in having more dorsally-placed eyes, manifested in its smaller interorbital distance compared to the latter three species (42.6–48.7% HL vs. 49.1–59.5), and a combination of a mottled body and a rounded anterior profile of the lower jaw.